Improved Functionality of Exhausted Intrahepatic CXCR5+ CD8+ T Cells Contributes to Chronic Antigen Clearance Upon Immunomodulation - Kumashie, Kingsley Gideon; Cebula, Marcin; Hagedorn, Claudia; Kreppel, Florian; Pils, Marina C.; Koch-Nolte, Friedrich; Rissiek, Björn; Wirth, Dagmar (Frontiers in Immunology, 2021)
Chronic hepatotropic viral infections are characterized by exhausted CD8+ T cell in the presence of cognate antigen in the liver. The impairment of T cell response limits the control of chronic hepatotropic viruses. Immune-modulatory strategies are attractive options to re-invigorate exhausted T cells. However, in hepatotropic viral infections, the knowledge about immune-modulatory effects on the in-situ regulation of exhausted intrahepatic CD8+ T cells is limited. In this study, we elucidated the functional heterogeneity in the pool of exhausted CD8+ T cells in the liver of mice expressing the model antigen Ova in a fraction of hepatocytes. We found a subpopulation of intrahepatic CXCR5+ Ova-specific CD8+ T cells, which are profoundly cytotoxic, exhibiting efficient metabolic functions as well as improved memory recall and self-maintenance. The intrahepatic Ova-specific CXCR5+ CD8+ T cells are possibly tissue resident cells, which may rely largely on OXPHOS and glycolysis to fuel their cellular processes. Importantly, host conditioning with CpG oligonucleotide reinvigorates and promotes exhausted T cell expansion, facilitating complete antigen eradication. The CpG oligonucleotide-mediated reinvigoration may promote resident memory T cell formation and the maintenance of CXCR5+ Ova-specific CD8+ T cells in the liver. These findings suggest that CpG oligodinucleotide may preferentially target CXCR5+ CD8+ T cells for expansion to facilitate the revival of exhausted T cells. Thus, therapeutic strategies aiming to expand CXCR5+ CD8+ T cells might provide a novel approach against chronic liver infection.